Pursuing professional development - Bailey, Kathleen M (Heinle & Heinle, 2001)
Includes bibliographical references (p. 264-277); 13 chapters: Why bother with professional development; self-awareness and self-observation: cornerstones; reflective teaching: looking closely; teaching journals: pieces of the puzzie; using cases: strories in the air;...